Adorno and Arendt: Evil, Modernity and the Underside of Theodicy - Holden, Terence (Sophia, 2019)
The point of departure for this article is a comparative study of Adorno and Arendt on the question of evil and modernity. To be precise, I observe how Adorno and Arendt present us with very different ways of understanding radical evil as an expression of the modern project of acceleration. This divergence presents us with a problematic which does not fit easily into the framework of the contemporary post-metaphysical engagement with evil. The latter projects a relational, non-substantive concept of evil addressed under the order of collective memory and against the background of a normatively neutralized order of history. Yet I show, by tracing the continuities and discontinuities which exist between Arendt and Adorno's conceptualizing of radical evil, on the one hand, and the different elements of this contemporary engagement, on the other, how the initial problematic is symptomatic of a continuing investment in history and can only be addressed in terms of such an investment. This investment is the product of a dynamic between history and memory, informing the work of both thinkers, which partially intersects with the Hegelian strategy of theodicy. I thus conclude with a consideration of whether certain aspects of the latter should be rehabilitated.